2002
DOI: 10.4141/a02-005
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian responses of anestrous ewes to the "ram effect"

Abstract: Ungerfeld, R., Pinczak, A., Forsberg, M. and Rubianes, E. 2002. Ovarian responses of anestrous ewes to the "ram effect". Can. J. Anim. Sci. 82: 599-602. Ovarian responses to the "ram effect" were characterized in 11 anestrous Corriedale ewes. In seven ewes, there was a luteinizing hormone (LH) surge 36.7 ± 12.3 h (mean ± SEM) after ram introduction and a concurrent increase (P < 0.05) in serum follicle stimulating hormone (FSH). Ovarian responses (monitored ultrasonographically) were highly variable. One ewe h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…The depth of anoestrus is a factor often cited in the literature as influencing the response to the 'ram effect' (Rosa and Bryant, 2002;Ungerfeld et al, 2004). We tested the effectiveness of the 'ram effect' during early, middle and late anoestrus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The depth of anoestrus is a factor often cited in the literature as influencing the response to the 'ram effect' (Rosa and Bryant, 2002;Ungerfeld et al, 2004). We tested the effectiveness of the 'ram effect' during early, middle and late anoestrus.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal cycles included short cycles and delayed cycles. Short cycles were defined as cycles in which the concentration of progesterone was above 0.5 ng/ml for 1 to 2 days indicating that ovulation occurred, but the luteal phase was shortened to less than 3 days (Chemineau et al, 2006) and delayed cycles were defined as cycles in which the concentration of progesterone first rose above 0.5 ng/ml after day 7, indicating that the luteal phase was delayed (Ungerfeld et al, 2002). Examples of ovarian responses are shown in Figure 2.…”
Section: Hormone Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Olfactory signals, or pheromones, are perhaps the most important, and they can inhibit (e.g., block pregnancy [1]) or facilitate (e.g., synchronization of estrus [2][3][4]) the reproductive process. Arguably, the most profound facilitatory effect of male sociosexual stimuli identified to date is observed in ungulates such as sheep, in which exposure to males leads within minutes to a complete change in the female's reproductive status from quiescent to fertile [5][6][7]. Moreover, the epidermal pheromone of sheep and goats seems to encode specific information about male identity, as only unfamiliar (''novel'') males seem able to induce ovulation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…3,6 However, recent work has demonstrated that physical (and consequently olfactory, auditive and hearing) isolation between genders is dispensable for male effect usage based ovulation induction in sheep and goats. 3,7 However, these studies dissected the physiological response and ovulation parameters of omitting ram physical isolation for male effect, 3,7,8 but further reproductive parameters such as pregnancy and prolificacy rates remained to be described.…”
Section: Introductionmentioning
confidence: 99%